2021
DOI: 10.31083/j.jin2004088
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament light as a biomarker of axonal degeneration in patients with mild cognitive impairment and Alzheimer’s disease

Abstract: Cerebrospinal fluid neurofilament light and plasma neurofilament light concentrations are elevated in patients with mild cognitive impairment and Alzheimer's disease. We investigated the clinical relevance of increased neurofilament light concentrations in mild cognitive impairment and Alzheimer's disease patients. In this study, 244 subjects were divided into cognitively normal control (n = 67), stable mild cognitive impairment (n = 52), progressive mild cognitive impairment (n = 68), and Alzheimer's disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…These results are consistent with studies showing that verbal episodic memory is positively associated with hippocampus volume 38 and EC thickness 40 and negatively associated with plasma NfL levels 36 in individuals with DS across the AD spectrum. Plasma NfL levels were negatively correlated with bilateral hippocampus volume and left alEC thickness but not with other EC subregions, in line with findings in neurotypical individuals with and without symptomatic AD 8,41‐43 . In sporadic AD, gray matter loss occurs earlier and progresses faster in the left hemisphere 44 .…”
Section: Discussionsupporting
confidence: 80%
“…These results are consistent with studies showing that verbal episodic memory is positively associated with hippocampus volume 38 and EC thickness 40 and negatively associated with plasma NfL levels 36 in individuals with DS across the AD spectrum. Plasma NfL levels were negatively correlated with bilateral hippocampus volume and left alEC thickness but not with other EC subregions, in line with findings in neurotypical individuals with and without symptomatic AD 8,41‐43 . In sporadic AD, gray matter loss occurs earlier and progresses faster in the left hemisphere 44 .…”
Section: Discussionsupporting
confidence: 80%
“…Benedet et al [ 33 ] found that plasma NfLs negatively correlated with frontal and hippocampal GM and fronto-parietal WM volumes in healthy controls, and with wider fronto-temporal GM areas and whole-brain WM volumes in MCI and AD patients, at baseline and over time. Focusing on similar groups of subjects, Chen et al [ 35 ] found that higher CSF NfLs were associated with hippocampal atrophy in MCI patients and controls, and also with ventricular enlargement in AD patients; also, plasma NfLs were associated with the same measures in all the groups.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research indicates that NfL is a non-specific marker of neurodegeneration, with increased levels in CSF observed in various dementias [24]. Studies show that elevated levels of NfL in CSF and plasma are linked to AD-related neuroimaging findings, including hippocampal atrophy, ventricular enlargement, and cortical thinning [25][26][27]. Serum NfL levels also increase in healthy aging people and predict brain volume loss [28].…”
Section: Discussionmentioning
confidence: 99%